Measurement of the top-quark mass in all-jets $t\bar{t}$ events in pp collisions at $\sqrt{s}$=7 TeV - CMS collaboration (2210 authors) (2014)
The mass of the top quark is measured using a sample of $t\bar{t}$ candidate events with at least six jets in the final state. The sample is selected from data collected with the CMS detector in pp collisions at $\sqrt{s}$ = 7 TeV in 2011 and corresponds to an integrated luminosity of 3.54 inverse femtobarns. The mass is reconstructed for each event employing a kinematic fit of the jets to a $t\bar{t}$ hypothesis. The top-quark mass is measured to be 173.49 $±$ 0.69 (stat.) $±$ 1.21 (syst.) GeV. A combination with previously published measurements in other decay modes by CMS yields a mass of 173.54 $±$ 0.33 (stat.) $±$ 0.96 (syst.) GeV.